2020
DOI: 10.1021/acs.jchemed.0c00777
|View full text |Cite
|
Sign up to set email alerts
|

Mindful Well-Being and Learning

Abstract: Stress and anxiety can interfere with learning, and for many people, studying chemistry is perceived as a stressful endeavor. The COVID-19 pandemic has provided an additional source of stress and anxiety for students and has brought focus to the importance of well-being in the learning process. An improved understanding of the relationship between well-being and learning coupled with experience with ways to mitigate stress and anxiety such as mindfulness practice can benefit both instructors and students navig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…Students needed to quickly establish new effective study habits while coping with the change. 40 To help students make this transition, faculty created highly structured learning modules. Highly structured pedagogical practices improve student learning 41 and increase students' final exam scores, particularly for students that struggle academically 42 and disadvantaged students.…”
Section: Lack Of Routine and Structurementioning
confidence: 99%
“…Students needed to quickly establish new effective study habits while coping with the change. 40 To help students make this transition, faculty created highly structured learning modules. Highly structured pedagogical practices improve student learning 41 and increase students' final exam scores, particularly for students that struggle academically 42 and disadvantaged students.…”
Section: Lack Of Routine and Structurementioning
confidence: 99%
“…Large groups of educators from diverse fields may be useful in bringing together various viewpoints, but effective online teaching requires more than knowledge about content, pedagogical practices, and technology. It requires unique knowledge about how pedagogical practices and technology can be best used in the teaching and learning of specific content, and this knowledge is unique for different disciplines. , This Journal has been quick to coalesce knowledge around teaching chemistry during the COVID-19 pandemic, with articles in this special issue that included descriptions of assessment, , at-home laboratory activities, accommodations for students, and even mental well-being …”
Section: Discussionmentioning
confidence: 99%
“…1,2 This Journal has been quick to coalesce knowledge around teaching chemistry during the COVID-19 pandemic, with articles in this special issue that included descriptions of assessment, 6,7 at-home laboratory activities, 8 accommodations for students, 9 and even mental well-being. 10 It is not surprising that the topics in this special issue were also frequently discussed in the online community of Strategies for Teaching Chemistry Online. Through its participation from members, SFTCO was well-suited to build a repertoire of knowledge to meet the shared challenge of teaching chemistry during the COVID-19 pandemic.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Moreover, evidence suggests that the SARS-CoV-2 pandemic has increased the amount and types of stress, and coping mechanisms, used by chemistry educators in dramatic yet largely unmeasured amounts. 13,14 Although these observations barely scratch the surface of the pertinent literature on stress in educational settings, they constitute ample evidence that the role of stress in teaching and learning chemistry is difficult to understand and visualize, as well as generally outside the professional training of chemistry teachers. So, a chemistry-based analogy is interesting to explore.…”
mentioning
confidence: 99%
“…Notably, in several cases where STEM faculty members were compared to faculty in other departments, the study suggested that STEM faculty report higher levels of stress. Moreover, evidence suggests that the SARS-CoV-2 pandemic has increased the amount and types of stress, and coping mechanisms, used by chemistry educators in dramatic yet largely unmeasured amounts. , …”
mentioning
confidence: 99%